Campur Kode dan Alih Kode dalam Film Mungkin Esok, Lusa, atau Nanti Karya Iwan Kurniawan - Cahyati, Ica; Juidah, Imas; Logita, Embang (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: There was code mixing and code changes in the movie. The main point of this piece might be tomorrow, the day after tomorrow, or later. Objectives: The main goal of this work is so find and study the different kinds of code mixing and code flipping that occur when characters talk. The goal of this study is to find the different kinds of code mixing and code swapping and the factors that affect how they are used. Methods: The qualitative method used in this study lets the researchers look at the data in great detail and figure how out social and cultural factors affect how people use words. The way used to collect data for this study is to listen and take notes. Results: Researchers watch the movie and pay close attention to the dialogue. They write down cases of code switching and code mixing. The results of the study show that code mixing can occur both inside and outside of a company. This is because of how different languages work together. Additionally, there are types of internal and external code swapping that demonstrate how characters adapt to various communication contexts. These results offer a more comprehensive understanding of the intrigue of language use in films and how it mirrors prevailing social reality. Conclusion: This study shows how several factors can influence code switching and code mixing in movies. Some of these are the presence of a third speaker, limited vocabulary, the background of the speakers, the conversation partners, and the topics being discussed. In this movie, we can see the use of various languages, such as Indonesian, Javanese, Turkish, and English, all of which play a role in creating code switching and code mixing. Keywords : Code mixing, code switching, movie, character, language